Daniel Webster and the unfinished Constitution - Hoffer, Peter Charles, 1944- (American political thought., 2021)
"Daniel Webster is known primarily as a politician and is often described as a member of the second generation of American founders, alongside Henry Clay and John C. Calhoun-a generation whose divisions and rivalries ultimately led to the fracture of the nation. But before he was a politician and diplomat, Webster was a lawyer who argued some of the most important constitutional cases of the time. His arguments in these cases went well beyond the mere application of the law and instead proposed expansions and innovations in constitutional interpretation to address enduring questions left unanswered by the first generation of American founders. Webster understood, in a way that many today do not, that the Constitution was never a finished text. Daniel Webster and the Unfinished Constitution explores Webster's legal thought and the vital contributions he made to constitutional jurisprudence. In cases such as Dartmouth College v. Woodward, McCulloch v. Maryland, and Gibbons v. Ogden-as well as his debates with Calhoun and Robert V. Hayne-he addressed the relationship between the federal government and the states, the relationship between law and politics, and the boundary between public interest and private right. Webster tried to close all three of these interpretive spaces in the Constitution during his career. This study of Daniel Webster's role as both a legislator and a litigator sheds light on the living character of the Constitution"--